APLIKASI SISTEM INFORMASI KUNTANSI DALAM PENYUSUNAN LAPORAN KEUANGAN - Sanjaya Alacsel (Journal Accounting International Mount Hope, 2023)
The aim of this study is to provide an overview to the service company that the importance of using accounting systems in compiling financial reports. So that the financial statements presented can be compiled quickly, accurately and completely compared to the financial records presented manually. With today's technological developments there are many types of accounting information systems or accounting applications that can be used by service companies in the preparation of financial reports. Such accounting application can be adapted to the needs of service companies. Based on the above research, it can be concluded that many service companies still use manual recording in the compilation of finance reports.